2017
DOI: 10.1080/23311908.2017.1403064
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental trends in semantic fluency in preschool children

Abstract: Semantic fluency is a measure of verbal functioning and cognitive flexibility. Its development is particularly rapid in preschool years. The goal of this study was to examine semantic fluency in preschool children in relation to child's age and gender. The sample for this study comprised 133 children aged 3-6 years (mean age = 56.7 months; SD = 11.1 months) from Canton Sarajevo, Bosnia and Herzegovina. In relation to child's gender, there were 62 girls (46.6%) and 71 boys (53.8%). We used three different seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this context, a large difference between 7-8 and 9-10 age groups was found in a semantic fluency experiment by [29] that included children as old as 16. Children show verbal improvement around 3-6 years old, like that in the results of [30] where the older children were asked to list as many animals, foods and musical instruments in 60 seconds. In [31] groups of 8, 12 and 21-year-olds were asked to list as many animals and furniture items as they could in 7 minutes, and the results showed that while the adults were capable of listing more items, the categories and semantic cluster retrieval processes were similar to the younger children group.…”
Section: Discussionmentioning
confidence: 62%
“…In this context, a large difference between 7-8 and 9-10 age groups was found in a semantic fluency experiment by [29] that included children as old as 16. Children show verbal improvement around 3-6 years old, like that in the results of [30] where the older children were asked to list as many animals, foods and musical instruments in 60 seconds. In [31] groups of 8, 12 and 21-year-olds were asked to list as many animals and furniture items as they could in 7 minutes, and the results showed that while the adults were capable of listing more items, the categories and semantic cluster retrieval processes were similar to the younger children group.…”
Section: Discussionmentioning
confidence: 62%
“…It is also known as semantic fluency helps in measuring verbal functioning and cognitive flexibility of developing children. Certainly, data from typical development indicates that vocabulary correlates highly with other language abilities and its development is particularly rapid in preschool years (12) . Moreover, it is the single best predictor of academic success for children starting school (13) .…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with a large data analysis conducted by Hyde and Linn who pointed that the gender differences were not so large at all and that in fact gender differences do not exist. 17 The gender effect in verbal fluency tasks has been explored in many studies most of the results indicate lack of gender effect or small gender effect. 18 On contrary, Feldman et al 19 in their study on 2156 socio-demographically diverse 1 and 2 years old American children found that there was significant effect of gender on vocabulary comprehension and vocabulary production, as girls scored significantly higher than boys.…”
Section: Discussionmentioning
confidence: 99%